Binary black hole mergers from merged stars in the Galactic field - Stegmann, Jakob; Antonini, Fabio; Schneider, Fabian; Tiwari, Vaibhav; Chattopadhyay, Debatri (Arxiv, 2022)
The majority of massive stars are found in close binaries which: (i) are prone to merge and (ii) are accompanied by another distant tertiary star (triples). Here, we study the evolution of the stellar post-merger binaries composed of the merger product and the tertiary companion. We find that post-merger binaries originating from compact stellar triples with outer semi-major axes $a_{\rm out,init}\lesssim10^1\,-\,10^2\,\rm AU$ provide a new way to form binary black hole mergers in the galactic field. By means of a population synthesis, we estimate their contribution to the total black hole merger rate to be $\mathcal{R}(z=0)=0.3\,-\,25.2\,\rm Gpc^{-3}\,yr^{-1}$. Merging binary black holes that form from stellar post-merger binaries have exceptionally low mass ratios. We identify a critical mass ratio $q\simeq0.5$ below which they dominate the total black hole merger rate in the field. We show that after including their additional contribution, the mass ratio distribution of binary black hole mergers in the galactic field scenario is in better agreement with that inferred from gravitational wave detections.
Version 1 vom 30 März 2022, Version 2 vom 27 Juni 2022
Gesehen am 17.10.2022